2023
DOI: 10.1093/sxmrev/qead027
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma for the treatment of erectile dysfunction: a systematic review of preclinical and clinical studies

Evangelos Poulios,
Ioannis Mykoniatis,
Nikolaos Pyrgidis
et al.

Abstract: Introduction There has been tremendous growth in regenerative medicine during the last decade. For erectile dysfunction (ED), after the inclusion of low-intensity shockwave therapy as a treatment modality for ED management by the European Association of Urology sexual health guidelines, intracavernosal injection of platelet-rich plasma (PRP) has gained popularity between urologists and patients as a novel ED therapeutic modality with initial promising results. However, limited clinical data e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…PRP injections have been associated with no serious adverse events, such as infection, bleeding, or nerve damage in multiple studies on wound care, orthopedics, urology, dental surgery and cosmetic procedures [12,54]. The latter is in line with our systematic review, which found that none of the included patients who received PRP injections developed serious adverse events and less than 1% of all patients (3/317) developed minor adverse events.…”
Section: Discussionsupporting
confidence: 84%
“…PRP injections have been associated with no serious adverse events, such as infection, bleeding, or nerve damage in multiple studies on wound care, orthopedics, urology, dental surgery and cosmetic procedures [12,54]. The latter is in line with our systematic review, which found that none of the included patients who received PRP injections developed serious adverse events and less than 1% of all patients (3/317) developed minor adverse events.…”
Section: Discussionsupporting
confidence: 84%
“…They found that 22/29 (76%) reached IIEF minimum clinically important difference (MCID) in the PRP group, compared to only 7/28 (25%) in the placebo group at 6 months. MCID are patient derived scores that re ect changes in a clinical intervention that are meaningful for the patient and based on IIEF-EF score is de ned as an increase of ≥2 for patients with baseline mild ED (baseline IIEF-EF score of 17-25), and ≥5 for patients with baseline moderate ED (score of [11][12][13][14][15][16]. ED categories based on the IIEF-EF score: no ED (26-30), mild (17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (11)(12)(13)(14)(15)(16), and severe (0-10) (20).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the therapeutic qualities of growth factors found in high quantities in this fraction, many medical disciplines have utilized PRP injections in their therapy choices (11). PRP intracavernosal injections have recently emerged as a promising angiogenic, vasculogenic, and regenerative therapeutic option for ED (13).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that, in this case, differences in patient population and trial design do not allow direct comparisons to any previous trial. 3…”
mentioning
confidence: 99%